Pengaruh Komunikasi Pastoral dalam Terang Ensiklik Fratelli Tutti terhadap Relasi Sosial Umat Stasi Santo Adrianus Ranokolo, Paroki Santo Yohanes Paulus II Ropa - Marfin Tharesa Bheti; Florens Maxi Un Bria; Yohanes Rusae (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
Pastoral communication is one of the Church's ministries that plays an important role in fostering social relationships, strengthening fraternity, and nurturing mutual care among the faithful within the life of the Church. This study aims to identify the forms of pastoral communication and analyze their influence on the social relationships of the faithful at St. Adrianus Ranokolo Outstation, St. John Paul II Ropa Parish, in the light of the Encyclical Fratelli Tutti. The study employed a qualitative research method with a descriptive approach. Data were collected through observation, interviews, and documentation involving the parish priest, the outstation leader, members of the Parish Pastoral Council, and parishioners as informants. The findings reveal that pastoral communication is carried out through pastoral visits, community meetings, liturgical celebrations, neighborhood prayer gatherings, pastoral accompaniment, and the use of communication media. These forms of pastoral communication have a positive influence on the social relationships among the faithful, as reflected in increased cooperation, solidarity, social concern, unity, and active participation in various Church activities. In the light of the Encyclical Fratelli Tutti, the practice of pastoral communication embodies the values of fraternity, dialogue, solidarity, and love for one's neighbor, thereby contributing to the development of a harmonious Christian community and strengthening social relationships within the Church.